Radiological Imaging Evaluation of the Failing Total Hip Replacement - Mushtaq, Nida; To, Kendrick; Gooding, Chris; Khan, Wasim (Frontiers in Surgery, 2019)
Total hip arthroplasties (THA) have been performed in the UK from the 1960s and since then we have seen surgical techniques, the design of implants and imaging modalities rapidly develop. This paper will aim to review the different complications and imaging appearance which help to evaluate each problem. As for all initial bone and joint investigations, a radiograph is the first imaging to be performed for any patient with a total hip replacement and can detect a majority of complications. CT is relatively inexpensive, readily available and easy to perform making it an excellent tool to supplement radiographs when trying to evaluate a hip prosthesis. Single photon emission computed tomography with CT (SPECT-CT) is an emerging diagnostic modality which has shown to combine the sensitivity that bone scintigraphy offers with the high specificity of CT. SPECT imaging has the advantage of showing the metabolic activity of the bone surrounding the prosthesis and is less prone than MRI to metal artefact. Magnetic resonance imaging (MRI) has evolved to become an important diagnostic tool for the evaluation of hip arthroplasty in the post-operative period. Optimised pulse sequences and metal artefact reduction techniques have made MRI a useful tool in diagnosis of periprosthetic fractures, bone resorption and osteolysis, soft tissue reactions and neurovascular compromise. CT and MRI are accurate in identifying the diagnosis of most causes of hip arthroplasty complications except infection. Research confirms that leukocyte/marrow imaging is the modality of choice for accurately diagnosing prosthetic joint infection and reassures us of its superiority over other nuclear medicine imaging. Ultrasound (US) is not recommended as the first line examination to assess peri-prosthetic bone complications due to the deep location of the hip prosthesis and the inability of the sound to penetrate bone or metal. However, US still has a role in identifying peri-prosthetic fluid collections and the presence of sinus tracts within soft tissues. We conclude that although imaging is not performed by orthopaedic surgeons, an understanding of the radiological appearances of these complications along with the advantages and disadvantages of each modality will ensure optimal patient care.